Working Memory Goes to School. Issue 3 (2nd July 2016) - Prince, Pauline; Gifford, Kathleen
Abstract : This article endeavors to provide a comprehensive developmental perspective of Working Memory in the classroom. Instructional implications will be discussed as they apply to preschool, elementary and secondary education. It is the intent of this paper to also provide food for thought about working memory as it applies to other aspects of the school day, such as physical education and social, emotional, and behavioral functioning.